OOn the issue of professional pension risks in the Republic of Kazakhstan - Saktaganova , Indira; Smatlaev, Baurzhan; Issayeva , Ainur (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
This article covers a current topic professional pension provision for those employed under hazardous and difficult working conditions, the international experience of professional pension schemes, and stages in creating one in Kazakhstan. To identify and set compensation for employees who worked under harmful and/or other adverse working conditions, determine employer participation levels in production processes, as well as assess any required capital investments by employers to enhance working conditions. This article presents an in-depth examination of Kazakhstan's existing pension system with respect to occupational risks faced by employees from various sectors of its economy. Additionally, its effectiveness was evaluated within a context of demographic shifts, labor market transformation and an increase in informal sector workers. Recommendations are made for strengthening the pension system to ensure its sustainability and adaptability with changing socio-economic conditions, with comparisons made against international best practices as well as suggestions on integrating them into Kazakhstani society. The authors propose a set of measures aimed at strengthening the professional pension system, such as strengthening its regulatory framework and activating investment activities of pension funds, developing tools to encourage employers to improve working conditions, increasing financial transparency and increasing financial responsibility.